Bcl-2 functionally interacts with inositol 1,4,5-trisphosphate receptors to regulate calcium release from the ER in response to inositol 1,4,5-trisphosphate. - Chen, R; Valencia, I; Zhong, F; McColl, K; Roderick, H; Bootman, MD; Berridge, M; Conway, S; Holmes, AB; Mignery, G; Velez, P; Distelhorst, C (2004)
Inositol 1,4,5-trisphosphate (InsP3) receptors (InsP3Rs) are channels responsible for calcium release from the endoplasmic reticulum (ER). We show that the anti-apoptotic protein Bcl-2 (either wild type or selectively localized to the ER) significantly inhibited InsP3-mediated calcium release and elevation of cytosolic calcium in WEHI7.2 T cells. This inhibition was due to an effect of Bcl-2 at the level of InsP3Rs because responses to both anti-CD3 antibody and a cell-permeant InsP3 ester were decreased. Bcl-2 inhibited the extent of calcium release from the ER of permeabilized WEHI7.2 cells, even at saturating concentrations of InsP3, without decreasing luminal calcium concentration. Furthermore, Bcl-2 reduced the open probability of purified InsP3Rs reconstituted into lipid bilayers. Bcl-2 and InsP3Rs were detected together in macromolecular complexes by coimmunoprecipitation and blue native gel electrophoresis. We suggest that this functional interaction of Bcl-2 with InsP3Rs inhibits InsP3R activation and thereby regulates InsP3-induced calcium release from the ER.